2011
DOI: 10.2174/1874294701105010014
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Distribution of Roots of Dioscorea Alata L. Do Not Respond to Mineral Fertiliser Application

Abstract: Water yam (Dioscorea alata) is a staple crop for many of the poorest in the tropics. Yam tuber response to fertiliser application has been reported to be erratic. We hypothesised that this variable response could be due to the development of a suboptimal root system that would not allow the plant to capture the nutrients added with the fertiliser. To verify this hypothesis we studied during two seasons (2006 and 2007) in Central Côte d'Ivoire, the growth of yam root system in relation to plant growth as affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…The maximum RLD of 0.26 cm cm (3 observed in D. rotundata was smaller than the maximum RLD of 11.3 and 1.5 cm cm (3 , reported for potatoes (Ahmadi et al 2011) and cassava (Lose et al 2003), respectively. The root spatial distribution pattern observed in this study showed that D. rotundata is also a shallow-rooting species, similar to D. esculenta (Melteras et al 2008), D. alata (Hgaza et al 2011), cassava (Lose et al 2003) and potatoes Groenwold 1986, Ahmadi et al 2011).…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…The maximum RLD of 0.26 cm cm (3 observed in D. rotundata was smaller than the maximum RLD of 11.3 and 1.5 cm cm (3 , reported for potatoes (Ahmadi et al 2011) and cassava (Lose et al 2003), respectively. The root spatial distribution pattern observed in this study showed that D. rotundata is also a shallow-rooting species, similar to D. esculenta (Melteras et al 2008), D. alata (Hgaza et al 2011), cassava (Lose et al 2003) and potatoes Groenwold 1986, Ahmadi et al 2011).…”
Section: Discussionsupporting
confidence: 63%
“…No roots were observed below a depth of 15 cm at a distance of 50 cm from the crown (i.e. outside the mound) by Hgaza et al (2011). While shoot and tuber production were significantly increased by mineral fertilizer application, these authors did not observe any significant effect of the applied fertilizer on root growth and distribution.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…batatas ; 25%] (Hartemink et al, 2000) but lower than in potato ( Solanum tuberosum L.; 61%) (Darwish et al, 2006). This result suggests that although D. alata has been described as a shallow‐rooting species with low root density and heterogeneous distribution (Hgaza et al, 2011), it can capture the applied N efficiently.…”
Section: Discussionmentioning
confidence: 97%
“…The amplitude of this “priming effect” in this low‐N soil must nevertheless be emphasized. If we assume that most of the N taken up by the plant is derived from the mound and from the surrounding surface soil that was explored by roots as observed by Hgaza et al (2011), and if we consider that the total N content of the foraged horizon is 0.7 g N kg −1 soil (Table 1) with an apparent density of 1.3 Mg m −3 , then the uptake of 205 kg N ha −1 would represent about one‐seventh of the total soil N. These low soil total N contents have already been reported in this region of West Africa (e.g., Nacro et al, 1996, 2004), and our results suggest that the rate of mineralization of soil organic matter can be very high. These results suggest that intensive yam cultivation in this region should always be accompanied by a proper scheme of organic matter management, without which soil organic matter depletion would occur rapidly.…”
Section: Discussionmentioning
confidence: 99%